Banks, low interest rates, and monetary policy transmission - Olivier Wang (European Central Bank (ECB), 2020)
This paper studies how low interest rates weaken the short-run transmission of monetary policy and contract the long-run supply of bank credit. As U.S. bond rates have fallen, the pass-through of monetary shocks to loan and deposit rates has weakened while the spread on U.S. bank loans has risen. I build a model in which banks earn deposit and loan spreads, deposits compete with money, and banks' lending capacity depends on their equity. The short-run transmission of monetary policy is dampened at low rates, because deposit spreads act as a better hedge for bank equity against unexpected monetary shocks. In the long run, persistent low rates decrease banks' "seigniorage" revenue from deposit spreads, hence bank equity and loan supply contract, and loan spreads increase.
Keywords: E4; E5; G21; 330; low interest rates; financial intermediation; interest rate pass-through; deposit spread; loan spread